Tikomprotendis Learning Video Media Assisted by Prezi Increases Science Learning Outcomes - I Putu Gede Bagus Tedja Divayuda; Ni Ketut Suarni; I Made Gunamantha (Universitas Pendidikan Ganesha, 2026)
Student’s low learning outcomes due to lack of innovation in learning was a big problem. This research aimed to develop Tikomprotendis learning video media assisted by Prezi to improve science and science learning outcomes on technology topics for life in class V. This research is a development research with the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The product developed was validated by two material experts, two language experts and two media experts, 6 practitioners, namely teachers and 19 students. Data was collectedusing test and non-test techniques. Test techniques are used to obtain learning outcome data while non-test techniques are used to obtain product validation scores. Data from expert and practitioner tests is analyzed through averages and percentages. Meanwhile, the learning outcomes data were analyzed using a one group pretest-posttest only experimental design via a paired sample t-test. The research results show that; (1) Prezi-assisted learning video media is proven to be valid in terms of media and material through expert validity testing by obtaining very high validity criteria. So it can be said that the Prezi-assisted learning video media was valid and suitable as a learning resource. (2) The Prezi-assisted learning video media was proven to be practical through practitioner tests with practicality assessment criteria and a practical category was obtained. So, it can be said that Prezi-assisted learning video media was practical to use as a learning resource. (3) Prezi-assisted learning video media has been proven to be effective in influencing the improvement of science and science learning outcomes for class V students through the paired sample t-test (t=18.645, P<0.05) with an effect size of 4.27 which was relatively high.